Pemikiran Filosofis Ekonomi Islam pada Masa Daulah Umayyah di Andalusia - Komala Sari, Windi; Hidayati, Tri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article aims to examine the philosophical thought of Islamic economics during the Umayyad dynasty in Andalusia, using a historical-philosophical approach, relying on data from various primary and secondary sources in the form of scientific literature (library research). The analysis was carried out to understand the economic concepts that developed during that period, including fiscal policy, trade systems, and resource management during the Umayyad dynasty in Andalusia. The research results show that the Umayyad Daula in Andalusia succeeded in creating an advanced economy through implementing economic policies based on justice and social welfare, such as implementing zakat, productive land management, and fair market regulation. Namely, the Islamic economy of the past can be an inspiration in designing a sustainable and just economic system in the modern era.